Type 2 diabetes significantly modulates the power of lipoprotein(a) to predict cardiovascular events and mortality in young coronary artery disease patients. (14th October 2021) - Mader, A; Maechler, M; Larcher, B; Sprenger, L; Mutschlechner, B; Benda, M; Leiherer, A; Muendlein, A; Vonbank, A; Drexel, H; Saely, C H
Abstract: : Lipoprotein(a) [Lp(a)] is an important cardiovascular risk factor especially in young individuals. The purpose of this study was to investigate whether Lp(a) has the power to predict cardiovascular events in young coronary artery disease (CAD) patients with type 2 diabetes (T2DM). Lp(a) was measured in a cohort of 731 patients with angiographically proven CAD who were aged <65 years. Vascular events were recorded over a mean follow-up of 6.6±3.2 years. At baseline, 216 patients had T2DM, and 515 did not have diabetes. During follow-up, 30.2% of our patients suffered cardiovascular events. Lp(a) proved to be a strong and independent predictor of vascular events in the total study cohort (standardized adjusted HR=1.30 [1.07–1.56]; p=0.007). In subgroup analyses by diabetes status, Lp(a) significantly predicted vascular events in non-diabetic patients (standardized adjusted HR= 1.39 [1.12–1.74]; p=0.003) but not in diabetic patients (standardized adjusted HR=0.93 [0.63–1.38]; p=0.731). An interaction term Lp(a) x T2DM was significant (p=0.002), indicating that T2DM significantly modulated the power of Lp(a) to predict cardiovascular events. We conclude that Lp(a) significantly modulates the power of Lp(a) to predict cardiovascular events in CAD patients <65 years. FUNDunding Acknowledgement: Type of funding sources: None.